Guanidine Synthesis: Use of Amidines as Guanylating Agents. Issue 5 (17th February 2016) - Baeten, Mattijs; Maes, Bert U. W.
Abstract: The use of amidines for the tandem or one‐pot synthesis of guanidines is reported. Guanidines are obtained by oxidative rearrangement of readily available and stable amidines into carbodiimides, followed by in situ reaction with amines. The protocol can be executed under mild reaction conditions (30 °C), in a green solvent (dimethyl carbonate). The amine scope is broad, including sterically hindered, oxidation‐sensitive and chiral amines. Examples for the synthesis of both acyclic and cyclic guanidines are provided. 2‐Propoxyphenyl iodide (2‐PrOPhI) by‐product, generated from the oxidant [ N ‐( p ‐toluenesulfonyl)imino](2‐propoxyphenyl)iodinane (2‐PrOPhINTs), can be isolated in high yields making regeneration of the hypervalent iodine reagent possible. The utility and greenness of the synthetic method versus the state‐of‐the‐art is demonstrated by a new route towards the antihypertensive drug Pinacidil. The process mass intensity (PMI) of the new route is only 24% of the classical one. Abstract :